Association between obesity and circulating tumor cells in early breast cancer patients - Tzschaschel, Marie Lena Johanna; Friedl, Thomas W. P.; Schochter, Fabienne; Schütze, Sabine; Polasik, Arkadius Andreas; Fehm, Tanja; Pantel, Klaus; Schindlbeck, Christian; Schneeweiss, Andreas; Schreier, Jörg; Tesch, Hans; Lorenz, Ralf Roland; et al. (Clinical breast cancer, 2023)
Background - Obesity and the presence of circulating tumor cells (CTCs) before and/or after chemotherapy are associated with poor outcome in breast cancer (BC) patients. The activation of oncogenic pathways in fatty tissue leads to cell proliferation, suggesting a possible link between obesity and CTCs. - Materials and Methods - In the phase III SUCCESS A trial, 3754 patients with early BC were randomized to 3 cycles of fluorouracil, epirubicin and cyclophosphamide followed by 3 cycles of docetaxel with or without gemcitabine. Data of 1088 patients with CTC assessments (CellSearch-System; Menarini Silicon Biosystems, Italy) and body mass index (BMI) measurements both before and after chemotherapy were available. Patients were classified according to the WHO's international definitions as underweight, normal weight, overweight, or obese, and according to their weight-change during chemotherapy into a weight-loss group (> 5% decrease), stable-weight group (≤ 5% weight-change) or weight-gain group (>5% increase). Associations between CTC positivity and, BMI or weight-change group were analyzed using frequency-table methods. - Results - At study entry, 47.4% patients were underweight or normal weight, 33.6% were overweight and 18.9% were obese. Before and after chemotherapy, CTCs were detected in 20.1% and 22.6% of patients, respectively. There was no association between CTC positivity and BMI before (P = 0.104) or after (P = 0.051) chemotherapy. Furthermore, there was no association between weight-change group and CTC status before/after chemotherapy (P = 0.332). - Conclusions - According to our analysis, the risk factors obesity and prevalence of CTCs are not associated and may represent independent prognostic factors.